2013
DOI: 10.1161/jaha.113.000117
|View full text |Cite
|
Sign up to set email alerts
|

T‐Helper Type 1 Bias in Healthy People Is Associated With Cytomegalovirus Serology and Atherosclerosis: The Multi‐Ethnic Study of Atherosclerosis

Abstract: BackgroundAlthough T‐helper type 1 (Th1) cells are considered important in atherosclerosis, the relationships between Th1 and Th2 cells and atherosclerosis have not been examined in population‐based studies.Methods and ResultsWe measured Th cells as a percentage of lymphocytes by flow cytometry using CD4 staining (%CD4) in 917 participants of the Multi‐Ethnic Study of Atherosclerosis. We also measured interferon gamma–positive and interleukin‐4‐positive CD4+ cells, representing Th1 and Th2 subpopulations (%Th1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 61 publications
8
66
0
Order By: Relevance
“…These results were consistent with a pro-atherogenic role for Th1 cells and an anti-atherogenic role for Th2 cells, and is the first demonstration of these relationships in a multi-ethnic population[21]. In addition, the degree of chronic adaptive immune activation, as estimated by higher memory and lower naïve CD4 + cell phenotypes, was associated with subclinical atherosclerosis and type 2 diabetes.…”
Section: Biomarker Domains Measured In Mesasupporting
confidence: 82%
See 1 more Smart Citation
“…These results were consistent with a pro-atherogenic role for Th1 cells and an anti-atherogenic role for Th2 cells, and is the first demonstration of these relationships in a multi-ethnic population[21]. In addition, the degree of chronic adaptive immune activation, as estimated by higher memory and lower naïve CD4 + cell phenotypes, was associated with subclinical atherosclerosis and type 2 diabetes.…”
Section: Biomarker Domains Measured In Mesasupporting
confidence: 82%
“…Results from variability studies demonstrated that these cellular phenotypes were reproducible and generally stable, indicating, for the first time, their suitability for evaluation in epidemiological research[21]. …”
Section: Biomarker Domains Measured In Mesamentioning
confidence: 99%
“…29,30 Furthermore, Th1 cytokines are prevalent in both human and murine atherosclerotic lesions. 15,31 Studies in mice with a deficiency of IFN-γ, IFNGR1, or the Th1 differentiating factor T-bet resulted in diminished atherosclerosis, indicating the importance of this Th1 response.…”
Section: Ifns In Atherosclerosismentioning
confidence: 99%
“…32 Recently we have shown that circulating levels of Th1 had significant positive associations with both CAC and cIMT in 917 men and women from the US general population. 38 The significant associations were independent of traditional and novel risk factors including CRP and sICAM-1. Though the study was cross sectional, currently a large epidemiological study is ongoing to examine a longitudinal association of T cell phenotypes including Th1 with cardiovascular outcomes.…”
Section: Potential Mechanisms Of High-dose Lcn-3 Pufas On Atherosclermentioning
confidence: 92%